Conflict Resolution in Papua Using a Social Reconstruction Approach - Kadek Deddy Tara; I Gede Sumertha KY; Djayeng Tirto; Achmed Sukendro; Pujo Widodo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The problem of High Social Gap in Papua is an indication of the causes of marginalization and discrimination against the Papuan people. The difference in perceptions of some Indonesian people at home and abroad regarding the armed separatist conflict is a push factor to corner the Indonesian government. Apart from that, the issue of the internationalization of the 1969 referendum mechanism, violations of Human Rights (HAM), and the management of Natural Resources (SDA) by multinational companies which did not have an impact on improving the welfare of the Papuan people also complement the opinion of the government's failure. Based on the background of the problem, this research uses qualitative research methods and a descriptive approach. The research results show that conflict resolution in Papua can be implemented through (three) things, namely the first, the gradual development of an Integrated Food Estate (IFE) according to traditional areas in Papua, which will indirectly support the realization of Territorial Resilience and the Universal Defense System (Sishanta). Furthermore, to ensure that all these processes are carried out well and continuously, it is necessary to form an Integrated Solution Center (ISC). To eliminate the issue of internationalization of Papua, it is necessary to implement International Defense Diplomacy (IDD) carried out by Indonesian government agents abroad to socialize International Laws which are the juridical basis that Papua is part of the Unitary State of the Republic of Indonesia (NKRI). By implementing all these recommendations, it is hoped that a peaceful and prosperous Papuan society will soon be realized.